Biology - Campbell, Neil A., 1946-2004.; Reece, Jane B. (San Francisco : Pearson, Benjamin Cummings, 2005)
The new edition of this introductory text first published in 1987 features strengthening of some themes--e.g. the process of science, science and society, evolution
Includes index.
System requirements for accompanying CD-ROM: Windows and Macintosh.
Keywords: Biology